2022
DOI: 10.2196/32002
|View full text |Cite
|
Sign up to set email alerts
|

How We Can Reap the Full Benefit of Teleconsultations: Economic Evaluation Combined With a Performance Evaluation Through a Discrete-Event Simulation

Abstract: Background In recent years, the rapid development of information and communications technology enabled by innovations in videoconferencing solutions and the emergence of connected medical devices has contributed to expanding the scope of application and expediting the development of telemedicine. Objective This study evaluates the use of teleconsultations (TCs) for specialist consultations at hospitals in terms of costs, resource consumption, and patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Many of the surveyed papers studied HOFs using specific technologies including mental health consultation [20,21], online consultations [22,32], clinical decision support systems (CDSS) [23], electronic medication management systems [24], video consultation [25][26], aged care systems [27] and telemedicine [36]. The context of use for these systems included hospitals [23,[28][29][30][31][32][33][34], residential aged care homes [27], and community health facilities [35]. Eleven papers were review papers and described a range of technology, users, and processes [20-22, 26-27, 31, 37-41].…”
Section: Structuresmentioning
confidence: 99%
See 4 more Smart Citations
“…Many of the surveyed papers studied HOFs using specific technologies including mental health consultation [20,21], online consultations [22,32], clinical decision support systems (CDSS) [23], electronic medication management systems [24], video consultation [25][26], aged care systems [27] and telemedicine [36]. The context of use for these systems included hospitals [23,[28][29][30][31][32][33][34], residential aged care homes [27], and community health facilities [35]. Eleven papers were review papers and described a range of technology, users, and processes [20-22, 26-27, 31, 37-41].…”
Section: Structuresmentioning
confidence: 99%
“…Some papers presented innovative approaches for understanding and helping understand micro level system behaviours. Hueget et al [32] studied economic viability of a teleconsultation system and showed that attention must be paid to characteristics of the system's users, as it influences system performance and outcomes such as cost-efficiency. Their approach used a novel discrete simulation system to better understand user scenarios and how different system configurations impact economic outcomes of the system [32].…”
Section: Micromentioning
confidence: 99%
See 3 more Smart Citations